PENGENDALIAN STOK BAHAN UTAMA PADA PRODUKSI KORAN DI PT. XYZ DENGAN MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY (EOQ) PROBABILISTIC - Muhammad Dhany Aprilia Pratama april; Fitriani Surayya Lubis; Misra Hartati; Harpito Harpito; Rika Taslim (Indragiri Islamic University, 2023)
This research discusses a company engaged in printing newspapers or newspapers. There are 3 main ingredients in making newspapers, namely stencil paper, plate cleaning liquid and plate. The problem faced by the company is that the supply of the main ingredients has weaknesses, including delays in fulfilling the demand for the main ingredients with the uncertainty of the company's demand with the supplier of the main ingredients for making newspapers. The purpose of this research is to determine the number of main raw material stocks in newspaper production using the probabilistic economic order quantity (EOQ) method so as to minimize the total inventory cost. Mapping of the main material requirements using forecasting, calculation of economic order quantity (EOQ) probabilistic and calculation of inventory costs and the difference in savings in total inventory costs. The results of the probabilistic economic order quantity (EOQ) are 1 roll of stencil paper, 1 jug of plate cleaning liquid and 16 boxes of plates with a difference in cost savings of Rp. 108,867,156.